Its Uses in Composite Bodies and Lipophilic Nanofiltration
Patent Information
- Application Number
- KR1020227028117
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-17
- Filing Date
- 2021-01-06
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-01-06
Smart Images

Figure 112022084788126-PCT00024_ABST
Abstract
Description
Technology Field
[0001] The present invention has a porous layer (1) comprising oxide particles bonded to a porous substrate comprising fibers, preferably fibers of an electrically nonconductive material, and within the gaps of the substrate, one or more oxides selected from oxides of elements Al, Zr, Ti, and Si, preferably selected from Al2O3, ZrO2, TiO2, and SiO2, which are selected from each other and partially selected from oxides of elements Al, Zr, Ti, and Si, and on at least one surface, an additional porous layer (2) comprising oxide particles bonded to the layer (1), which comprises one or more oxides selected from oxides of elements Al, Zr, Ti, and Si, preferably selected from Al2O3, ZrO2, TiO2, and SiO2, wherein the oxide particles present in the layer (1) have an intermediate particle size larger than the oxide particles present in the layer (2), and the intermediate particle size (d) of the oxide particles in the layer (1) 50 ) is 0.5 to 4 μm, and the intermediate particle size (d) of the oxide particles in layer (2) 50 The invention relates to a composite body characterized by having a thickness of 0.015 to 0.15 μm, preferably 0.04 to 0.06 μm, and having one or more polymer coatings (PB) containing polysiloxanes on or above the layer (2), a method for manufacturing the corresponding composite body, and particularly to its use in lipophilic nanofiltration. Background Technology
[0002] Membranes have been used for some time for the separation of organic solutions. This involves separating dissolved impurities, catalysts, or valuable substances having a higher molecular weight than the solvent from the solvent.
[0003] Approximately 30 bar (30 * 10 5Due to the maximum flow rate of only 50 to 150 L / m²h in Pa (toluene flow rate, determined as specified in the example), the application of membranes available to date has been very limited. A significant increase in such flow rates will lead to much more widespread use of this technology, as it also directly enables applications in the petrochemical industry.
[0004] An increase in flow rate could be easily achieved by the performance of nanofiltration at high temperatures, for example, in the range of 120 to 200 °C. However, there are currently no available membrane materials that exhibit sufficiently high thermal stability at an acceptable manufacturing cost.
[0005] For example, the disclosed silicon-coated PAN membrane for nanofiltration from Evonik Resource Efficiency GmbH is trade name PURAMEM ® SELECTIVE, PURAMEM ® PERFORMANCE and PURAMEM ® It includes FLUX, and its application range is 20 to 40 bar (20 to 40 * 10 5 The maximum temperature is Pa) and 50 ℃.
[0006] Various attempts to manufacture membranes from thermally stable polymers have not been successful to date. This is typically because existing porous support structures fail when compressed under high pressure and high temperature, which prevents any additional flow through the membrane, or, in the worst case, when damage or cracking occurs in the membrane.
[0007] Membranes with fluoropolymer coatings are known from the field of gas separation. In WO 2007 / 149640 A2, Porogen proposed applying a fluoropolymer layer on top of a porous PEEK carrier (PEEK film). The problem here was that the fluoropolymer binds to the carrier through functional groups.
[0008] DE 198 38 800 proposes an electroseparator having a composite structure comprising a two-dimensional flexible substrate having a plurality of orifices and a coating present thereon. The material of the substrate is selected from metal, alloy, plastic, glass, and carbon fiber, or a combination of these materials, and the coating is a two-dimensionally continuous, porous, electrically nonconductive ceramic coating. The use of the ceramic coating promises thermal and chemical stability.
[0009] The fact that such a composite body can be modified with a polymer is described, for example, in EP 1925047 A1. However, the polymer used herein must have an essentially spherical structure and must be present within the composite body.
[0010] Professor James Economy's research team published a report on a research project for the fabrication of thin-film composite (TFC) membranes in which selected layers are applied to porous supports, such as polysulfone or ceramic membranes. http: / / economy.matse.illinois.edu / membrane.htm ).
[0011] DE 10139559 A1 describes a hybrid membrane in which a ceramic material is modified into an organic separation layer. These are described as having better long-term stability than membranes with a carrier made of polymer, but having a non-uniform polymer surface. However, DE 10208278 A1 describes a similar hybrid membrane in which the ceramic membrane is based on a polymeric carrier material, in particular a polymer nonwoven.
[0012] Multilayer, essentially ceramic composite materials are also already known in DE 10255121 A1. The composite materials described herein are used as battery separators.
[0013] Unpublished application EP 19217879.6 describes a composite body used as a gas separation membrane and having a layer based on a fluorine-containing polymer as a separation-active polymer layer. The problem to be solved
[0014] The problem that the present invention aims to solve is to provide a membrane material that does not have one or more of the disadvantages of membrane materials known from the prior art.
[0015] Surprisingly, it has now been discovered that it is possible to obtain a membrane that solves the above problem by applying a polymer coating containing polysiloxane to a composite body having a very smooth surface.
[0016] Therefore, the present invention provides a composite body as claimed in the claims and described in detail below, a method for manufacturing the composite body, and a use of the composite body. means of solving the problem
[0017] The present invention, more specifically, has a porous layer (1) composed of oxide particles bonded to a porous substrate comprising fibers, preferably fibers of an electrically nonconductive material, and within the gaps of the substrate, comprising one or more oxides selected from oxides of elements Al, Zr, Ti, and Si, preferably selected from Al2O3, ZrO2, TiO2, and SiO2, which are selected from each other and partially selected from oxides of elements Al, Zr, Ti, and Si, and on at least one surface, a further porous layer (2) comprising oxide particles bonded to the layer (1), which comprises one or more oxides selected from oxides of elements Al, Zr, Ti, and Si, preferably selected from Al2O3, ZrO2, TiO2, and SiO2, wherein the oxide particles present in the layer (1) have an intermediate particle size larger than the oxide particles present in the layer (2), and the intermediate particle size (d) of the oxide particles in the layer (1) 50 ) is 0.5 to 4 μm, and the intermediate particle size (d) of the oxide particles in layer (2) 50 The present invention provides a composite body characterized by having a thickness of 0.015 to 0.15 μm, preferably 0.04 to 0.06 μm, and having a polymer coating (PB) containing one or more polysiloxanes on or above the layer (2), a method for manufacturing the corresponding composite body and its use particularly in lipophilic nanofiltration, and a separation device comprising a composite material according to the present invention or a composite material manufactured according to the present invention. Specific details for implementing the invention
[0018] The composite body of the present invention has the advantage of having a very smooth surface with fine pores, and thus it is possible to apply a separation-active polymer layer or film having a substantially uniform thickness at all points.
[0019] In addition, the composite body of the present invention can be further processed by conventional methods and has the advantage of being sufficiently flexible, preferably sufficiently flexible, to provide membrane modules, particularly so-called spirally wound modules. These membrane modules are a conventional form of use for membranes. They are easy-to-handle assemblies, through which membranes installed inside can be introduced, for example, into industrial plants.
[0020] What can be achieved by uniform thickness is that the entire surface of the separation-active layer (polymer coating) has no defects, such as holes, and has homogeneous permeability on the surface. This can be detected by point flow measurement using a suitable gas.
[0021] The (gas) flow rate through the membrane according to the present invention may be greater than 200 GPU for carbon dioxide, preferably > 500 GPU. A flow rate of 1 GPU is 0.0027 m³ (STP) / (m²h bar) (0.0027 10 -5 It corresponds to ㎥ (STP) / (㎡h Pa)).
[0022] The homogeneous permeability of the membrane surface avoids preferential flow through some regions of the membrane and particularly quickly prevents damage to these regions by external substances that may be present at non-negligible concentrations, which would cause a rapid deterioration of separation performance in the corresponding sub-regions of the membrane.
[0023] The size of the oxide particles used ensures uniform impregnation of the substrate, preventing the formation of cavities and air entrainment within the composite body. This ensures that the composite body is not compressed under compressive stress and that its pore structure is not destroyed. Furthermore, it is possible to adjust the pore size of the composite body through the size of the oxide particles used.
[0024] When a suitable combination of substrates, including fibers, particularly nonwoven substrates, is used in combination with oxide particles, a tensile strength of > 40 N / m in the machine direction of the composite body according to the present invention can be achieved.
[0025] The composite material according to the present invention and its use as a membrane in lipophilic nanofiltration even at high temperatures makes it possible to directly process the material stream obtained at high temperatures in each manufacturing method, thereby eliminating the effort of cooling the material stream to be processed before lipophilic nanofiltration.
[0026] The composite body of the present invention, the method for manufacturing the composite body according to the present invention, and the use of the composite body according to the present invention are described below by way of example without any intention that the present invention is limited to these exemplary embodiments. Where ranges, formulas, or classes of compounds are specified below, they are intended to include the corresponding ranges or groups of compounds explicitly mentioned, as well as individual values (ranges), or all sub-ranges and sub-groups of compounds that can be obtained by omitting compounds. Where literature is cited in the context of this specification, its contents must fully form part of the disclosure of the present invention with respect to matters specifically mentioned. Where numerical values are provided below as %, they are weight % unless otherwise specified. Where averages, e.g., molar mass averages, are reported below, they are numerical averages unless otherwise specified. Where material properties, e.g., viscosity, gas flow, selectivity, etc., are mentioned below, they are properties of the material at 25 °C unless otherwise specified. Where a formula (empirical formula) is used in the present invention, the specified indices may be absolute numbers as well as average values. The index regarding polymeric compounds is preferably an average value.
[0027] A composite body according to the present invention has a porous layer (1) composed of oxide particles bonded to a substrate comprising one or more oxides selected from oxides of elements Al, Zr, Ti, and Si, preferably selected from Al2O3, ZrO2, TiO2, and SiO2, more preferably selected from Al2O3 and SiO2, on a porous substrate comprising fibers of an electrically nonconductive material and within the gap of the substrate, and has an additional porous layer (2) comprising oxide particles bonded to the layer (1), comprising one or more oxides selected from oxides of elements Al, Zr, Ti, and Si, preferably selected from Al2O3, ZrO2, TiO2, and SiO2, more preferably selected from Al2O3 and SiO2, on at least one plane, wherein the oxide particles present in the layer (1) have an intermediate particle size larger than the oxide particles present in the layer (2), and the intermediate particle size (d) of the oxide particles in the layer (1) 50 ) is 0.5 to 4 μm, and the intermediate particle size (d) of the oxide particles in layer (2) 50 The thickness is 0.015 to 0.15 μm, preferably 0.04 to 0.06 μm, and is characterized by having a polymer coating (PB) containing one or more polysiloxanes on or above the layer (2). In the context of the present invention, polysiloxane means organically modified or unmodified polysiloxane, often also referred to as silicon. Preferred polysiloxanes or silicons are those described in WO 2011 / 067054 A1.
[0028] The median particle size in the layer can be determined by collecting scanning electron microscope images (e.g., using a JEOL JSM IT300 scanning electron microscope) and performing image evaluation. Alternatively, the particle size of the particles used can also be determined according to ISO 13320 by a suitable instrument for particle size measurement by static light scattering (Mastersizer Hydro 2000S, Malvern Panalytical, Malvern, UK) before incorporation into the coating and dispersion. Such an instrument measures particle size with the aid of laser diffraction. For this purpose, the refractive index of the particles to be measured must be known and recorded in the software. To measure the particle size distribution, the solid material to be measured is stirred at 1750 rpm and dispersed in deionized water by adding ultrasound if necessary. A sufficiently large aliquot of the dispersed sample is pipetteed into the dispersion module of the measuring instrument, where the laser diffraction is 15% to 20%. Using a Mastersizer Hydro 2000S, the light intensity from two laser beams (wavelengths 633 nm and 466 nm) scattered by the sample is measured. The three-dimensional distribution of the scattered intensity is evaluated using Mie theory. This is used to determine the particle size and particle size distribution. The measurement results are also reported as a distribution curve; thus obtained is not only an explanation of the average particle size but also information regarding the minimum and maximum particles in the sample. d 50 represents the intermediate particle size. In this regard, d 50 50% of the volume-weighted size distribution refers to diameters smaller than this diameter. Therefore, the additional parameter is d as a measure of the minimum particle in the sample. 10 and d as a measurement of larger particles 90 is. d 10 and d 90 The closer this is, the narrower the particle size distribution becomes.
[0029] Oxide particles comprising or composed of oxides selected from Al2O3 and SiO2 are particularly preferred. Intermediate particle size (d) of 0.015 to 0.15 μm, preferably 0.04 to 0.06 μm. 50 A very particularly desirable oxide particle having ) is one based on or composed of SiO2. An example of a particularly desirable oxide particle is Aerosil by Evonik Resource Efficiency. ® or Aeroxide ® It is pyrolytic oxide particles supplied under a brand name or similar products from other suppliers.
[0030] A composite body according to the present invention, in which a polymer coating is not present, preferably has a Gurley number of 200 to 1700 sec, preferably 250 to 1200 sec, and more preferably 300 to 800 sec. The Gurley number can be determined, for example, before the application of the polymer coating.
[0031] The Gurley number is a measure of the air permeability of a porous material. It is defined as the time in seconds required to diffuse 100 cm³ of air through a 1 inch² sample under defined conditions. To determine this, a circular sample with a diameter of 44 mm is punched using a bundle punch. The sample to be inspected is checked on a light stage for defects, possibly holes. Only visually perfect samples are suitable for measurement. Before starting the measurement, ensure that the level is adjusted on the measuring instrument (Densometer model No. 4110N, Gurley Precision Instruments, Troy, NY) and that the outer cylinder is filled with Densometer oil from Gurley Precision Instruments up to the marked level. The Densometer test operation involves measuring the time required for a specific amount of air to flow through a specific sample area under uniform and gentle pressure. Compressed air is generated by an inner cylinder of the correct diameter and standard weight, which flows freely into a partially oiled outer cylinder to ensure airtightness.
[0032] The composite body according to the present invention preferably has a thickness of 100 to 400 μm, preferably 125 to 200 μm, and more preferably 130 to 170 μm. The thickness is determined by a Mitutoyo micrometer (Digimetic Micrometer MDC-25PX, 0-25 μm).
[0033] The composite body according to the present invention preferably has an average pore size of 60 to 140 nm, preferably 75 to 130 nm. The average pore size is determined by a gas flow pore measurement method as described below using a Porolux 1000 (Porometer, Eke, Belgium).
[0034] For this purpose, a circular sample with a diameter of 25 mm is punched from the material to be analyzed and dried in a drying cabinet at 100°C for 1 hour to remove moisture from the pores, and then immediately placed in Porefil wetting fluid so that all existing pores are filled with this liquid. Afterward, the sample is degassed in a desiccator by applying reduced pressure (150 mbar or 15 kPa) for a short time to ensure that all pores are filled with Porefil. The degassed sample is placed in the sample holder of the measuring instrument and the sample holder is tightened.
[0035] The determination of the pore radius distribution is based on the measurement principle of capillary flow poremetry. A sample moistened with a wetting liquid and degassed is subjected to a stepwise rising inert gas pressure (nitrogen) in a measurement cell, and the pore diameter corresponding to the applied pressure is emptied by the gas pressure. Simultaneously, the gas flow rate at the rising pressure is recorded. In successive pores, an exchange of the wetting liquid and nitrogen occurs. This continues until the relevant pore range is covered, that is, until the liquid is gone even from the smallest pores present in the measurement area. Afterward, the pressure in the measurement cell is lowered again, and the measurement is repeated for the now-dry sample. The pore size distribution is calculated using the difference between the wetting curve and the drying curve. Poremetry measurements provide information on the maximum existing pore radius ("bubble point") and the most typical and smallest pore diameters.
[0036] The composite body according to the present invention has a surface roughness Sdq on the surface of layer (2), which is determined as described below, preferably less than 10 μm, more preferably less than 8 μm.
[0037] Surface roughness is measured using a confocal microscope ( http: / / ak-rauheit.de / files / 3D%20Kenngr%F6%DFen.pdfIt is determined based on a measurement area of 2 cm * 2 cm measured by ). This determination can be performed, for example, using a Nanofocus, Oberhausen μsurf professional confocal microscope. This is done by using an 800xs type lens and scanning a 3 x 3 image. The evaluation is performed using μsoft Analysis Premium 7.4.8164 evaluation software on an unfiltered surface in accordance with DIN ISO 25178. The Rdq value is verified in accordance with DIN ISO 4287.
[0038] A preferred composite body according to the present invention has a Gurley number of 200 to 1700 sec, preferably 250 to 1200 sec, and more preferably 300 to 800 sec, a thickness of 100 to 400 μm, preferably 125 to 200 μm, and more preferably 130 to 170 μm, an average pore size of 60 to 140 nm, preferably 75 to 130 nm (preferably the outermost layer), and / or preferably a surface roughness Sdq of less than 10 μm, more preferably less than 8 μm, and a composite body having each of the most preferred parameters is particularly preferred.
[0039] In the composite body according to the present invention, the substrate is preferably a nonwoven fabric, knit or laminated scrim, preferably a nonwoven fabric or laminated scrim, more preferably a nonwoven fabric. The fibers preferably have fiber dimensions of 1 to 200 g / km. The fibers are preferably made of polyacrylonitrile, polyamide, polyester and / or polyolefin, preferably polyacrylonitrile. The fibers are more preferably made of polyacrylonitrile, polyamide, polyester and / or polyolefin, preferably polyester, in particular polyethylene terephthalate, having fiber dimensions of 10 to 80 g / km, and most preferably having fiber dimensions of 50 g / km.
[0040] The substrate preferably has a thickness of 50 to 150 μm, preferably 100 to 130 μm. The substrate preferably has a base weight of 40 to 150 g / m², preferably 50 to 120 g / m², preferably 50 to 100 g / m², and most preferably 60 g / m². More preferably, the substrate has a thickness of 50 to 150 μm, preferably 100 to 130 μm, and a base weight of 40 to 150 g / m², preferably 50 to 120 g / m², preferably 50 to 100 g / m², and most preferably 60 g / m².
[0041] A particularly desirable substrate is one that has all the parameters mentioned above, and most preferably has each of the most desirable parameters mentioned above.
[0042] Particularly suitable polymer coatings, including polysiloxanes, have a high intrinsic gas permeability to CO2 of > 200 barrer (cm³ / cm*sec*cmHg under standard conditions). Preferred polysiloxanes or silicones are, for example, polydimethylsilicon, polyethylmethylsilicon, nitrile silicone, polytrimethylsilylpropene, or otherwise, corresponding copolymers. The polymer coating (PB) preferably has a thickness of 0.05 µm to 10 µm, preferably 3 µm to 8 µm.
[0043] For the rapid characterization of composite bodies with polymer coatings, they were described by simple and reliable measurements of clean gas selectivity and flow rate. For this purpose, a specimen of a membrane with a diameter of 40 mm was introduced into a measurement cell for flat membranes. Subsequently, pressures of appropriate gases (first methane, then carbon dioxide) were applied to the membrane in a stepwise manner on the high-pressure side. Measurements were taken from 2 to 25 bar (2 to 25 * 10⁻⁶). 5 It was performed at a membrane penetration pressure of Pa. The amount of permeated gas was quantified using a Bronkhorst mass flow meter.
[0044] The obtained data was standardized using geometric data of the membrane measurement cell and expressed in relative terms. Clean gas selectivity is calculated using the ratio of the permeated gas volumes of different gases at the same membrane penetration pressure. For a defect-free membrane, this must be greater than 2.7 for carbon dioxide compared to methane. By appropriately standardizing the individual carbon dioxide flow rates through the membrane, for a sufficiently thin and defect-free polymer coating prepared by the method described herein, an average permeability of > 500 GPU (always combined with clean gas selectivity of > 2.7) can be easily calculated.
[0045] The composite body according to the present invention is preferably 130°C and 30 bar (30 * 10 5 At a membrane penetration pressure of Pa), the toluene flow rate is greater than 130 L / m²h, preferably greater than 250 L / m²h, more preferably greater than 300 L / m²h, and most preferably greater than 400 L / m²h, as determined as specified in the examples.
[0046] The composite body of the present invention is notable for its good stability during handling. This reduces the likelihood of defects or damage occurring in the composite body, for example, during introduction into a device for separating gas mixtures. Typical defects or damage would be breakage of the ceramic due to twisting or handling with a sharp object.
[0047] The composite body of the present invention preferably does not have any layer or coating comprising a fluorine-containing polymer.
[0048] The composite body according to the present invention is preferably flexible. In the context of the present invention, "flexible" means that it can be wound around a bar or tube with a diameter of 15 mm or less without damage. A particularly preferred composite body according to the present invention can be wound around a rod or bar having a minimum diameter of 5 mm or less without damage. That the corresponding composite body is not damaged can be easily proven by determining the gas flow of nitrogen. In this context, an increase of more than 100% in the gas flow determined by nitrogen is considered a defect / damage to the composite body. Due to the flexibility of the composite body according to the present invention, it can be introduced in a very simple manner in the form of typical modules for flat membranes and is particularly suitable for use in spirally wound modules, plate or frame modules, pocket modules, and other devices designed for flat membranes.
[0049] Due to the partial ceramic structure of the composite body according to the present invention, they also have the advantage that there is preferably little, and preferably no, change in their thickness and / or porosity under compressive stress. This enables the entire composite body to have substantially constant flow performance in the GPU even under high compressive stress, and has the advantage that this flow is not reduced at higher pressures by the compressive porous structure. To determine the change in thickness and / or porosity, a circular sample having a diameter of 35 mm can be cut from the composite body according to the present invention, and simultaneously with the determination of the thickness, a hydraulic press up to 52 bar (52 * 10⁻⁶) 5 A pressure of Pa can be applied (measuring instrument of INSTRON). A diagram plotting thickness as a function of compressive pressure can be used to calculate the elastic component of the change in thickness after three cycles of compressive stress and relaxation. For the composite body according to the present invention, this is preferably less than 8%, more preferably less than 7%.
[0050] The composite body according to the present invention can be manufactured in various ways; preferably, the composite body according to the present invention is obtained by the method according to the present invention described below.
[0051] A method according to the present invention for manufacturing a composite body, preferably a composite body according to the present invention, is characterized by the following steps:
[0052] (a) a step of applying a coating composition (BM1) to a substrate having gaps between fibers and fibers and within the substrate, wherein the coating composition is
[0053] (a1) selected from oxides of elements Ti, Al, Zr and / or Si, preferably selected from Al2O3, ZrO2, TiO2 and SiO2, more preferably selected from oxides of elements Al and Si, having an intermediate particle diameter (d) of 0.5 to 4 μm.50 A dispersion (D1) of oxide particles produced by mixing oxide particles having ) with water, an inorganic acid, preferably nitric acid, and a dispersion aid,
[0054] (a2) selected from oxides of elements Ti, Al, Zr and / or Si, preferably selected from oxides of elements Al and Si, and having an intermediate particle diameter (d) of 15 to 150 nm, preferably 40 to 60 nm. 50 A dispersion of oxide particles (D2) produced by mixing oxide particles having ) with water,
[0055] (a3) A binder formulation (BF1) produced by mixing two or more organic functional silanes with an alkanol, preferably ethanol, an inorganic acid, preferably boric acid, and water
[0056] Formed by combining,
[0057] (b) a step of incorporating a coating composition (BM1) at a temperature of 100 ℃ to 275 ℃, preferably 120 ℃ to 240 ℃ to produce a first layer (S1'),
[0058] (c) optionally applying a coating composition (BM2) to at least one layer (S1'), wherein the coating composition (BM2) is
[0059] (c1) Selected from oxides of elements Ti, Al, Zr and / or Si, preferably selected from Al2O3, ZrO2, TiO2 and SiO2, more preferably selected from oxides of elements Al and Si, having an intermediate particle diameter (d) of 0.5 to 4 μm. 50 A dispersion of oxide particles (D3) produced by mixing oxide particles having ) with water, an inorganic acid, preferably nitric acid, and a dispersion aid,
[0060] (c2) selected from oxides of elements Ti, Al, Zr and / or Si, preferably selected from Al2O3, ZrO2, TiO2 and SiO2, more preferably selected from oxides of elements Al and Si, with an intermediate particle diameter (d) of 15 to 150 nm, preferably 40 to 60 nm. 50 A dispersion of oxide particles (D4) produced by mixing oxide particles having ) with water,
[0061] (c3) A binder formulation (BF2) produced by mixing two or more organic functional silanes with an alkanol, preferably ethanol, an inorganic acid, preferably boric acid, and water.
[0062] Generated by combining,
[0063] (d) optionally incorporating the coating composition (BM2) at a temperature of 100 ℃ to 275 ℃, preferably 120 ℃ to 240 ℃ to produce a second layer (S2'),
[0064] (e) a step of applying a coating composition (BM3) to layer (S1') or, if present, layer (S2'), wherein the coating composition (BM3) comprises water and an inorganic acid
[0065] (e1) selected from oxides of elements Ti, Al, Zr and / or Si, preferably selected from Al2O3, ZrO2, TiO2 and SiO2, more preferably selected from oxides of elements Al and Si, having an intermediate particle diameter (d) of 25 to 100 nm, preferably 40 to 60 nm. 50 An aqueous dispersion (D5) containing oxide particles having ), and ethanol and
[0066] (e2) A binder formulation (BF3) comprising two or more organic functional silanes
[0067] Created by combining with,
[0068] (f) a step of incorporating a coating composition at a temperature of 100 ℃ to 275 ℃, preferably 120 ℃ to 240 ℃ to produce a layer (S3'),
[0069] (g) optionally applying a coating composition (BM4) to the layer (S3'), wherein the coating composition (BM4) comprises water and an inorganic acid
[0070] (g1) an aqueous dispersion (D6) comprising oxide particles selected from oxides of elements Ti, Al, Zr and / or Si, preferably selected from oxides of elements Al and Si, having an intermediate particle diameter of 15 to 150 nm, preferably 40 to 60 nm, and ethanol and
[0071] (g2) A binder formulation (BF4) comprising two or more organic functional silanes
[0072] Created by combining with,
[0073] (h) optionally incorporating a coating composition at a temperature of 100 ℃ to 275 ℃, preferably 120 ℃ to 240 ℃ to produce a layer (S4'),
[0074] (i) A step of applying a polymer coating containing polysiloxane to layer (S3') or, if present, layer (S4').
[0075] Polysiloxane refers to organically modified or unmodified polysiloxane, often also called silicon.
[0076] The composite body according to the present invention preferably does not include any step of applying a layer or coating comprising a fluorine-containing polymer.
[0077] Intermediate particle diameter (d) of 15 to 150 nm, preferably 40 to 60 nm 50Oxide particles having ) are particularly preferably used and are based on or made of SiO2. Corresponding particles are available, for example, from Evonik Resource Efficiency GmbH under the name Aerosil® Ox50.
[0078] In the preparation of binder formulations BF1 to BF2, it is preferable to use a sufficient acid with a pH of 2 to 5. In the preparation of coating compositions BM1 to BM4, it is preferable to use a sufficient amount of acid with a pH of 2.5 to 5. When the binder formulation is prepared using AMEO, the pH is preferably greater than 8, preferably 8.5 to 9.5. Particularly when AMEO is used in the binder formulation, it may be advantageous to combine the individual component steps of the binder formulation so that the feedstock of the binder formulation is metered directly into the coating composition without intermediate steps. However, this procedure is also applicable to all other coating composition formulations.
[0079] The dispersing aid used may be any suitable dispersing aid. It is designated DOLAPIX by Zschimmer & Schwarz GmbH & Co KG or TEGO by Evonik Resource Efficiency GmbH. ® It is preferable to use a dispersion aid sold under the name Dispers. The dispersion aid used is more preferably a carboxylic acid preparation sold, for example, by Zschimmer & Schwarz GmbH & Co KG under the name DOLAPIX CE 64.
[0080] In the method according to the present invention, it may be advantageous and therefore desirable to perform any steps (c), (d), (g), and (h), because in this way it is possible to more easily and reliably obtain a composite body having a low surface roughness, preferably less than 10 μm, and more preferably less than 8 μm, Sdq. Therefore, it is particularly desirable to perform all of steps (c) and (d) and steps (g) and (h). In this way, it is also possible to reliably avoid defects in the composite body, i.e., areas where there is a distinct deviation from the claimed values or the values described as preferred, for example, the average pore size, Gurley number, thickness, and / or surface roughness.
[0081] The organic functional silane used, preferably an alkoxy-functional silane, more preferably a methoxy- and / or ethoxy-functional silane, is preferably 3-glycidyloxytriethoxysilane, methyltriethoxysilane, octyltriethoxysilane, aminopropyltriethoxysilane and / or tetraethoxysilane. The organic functional silane used is preferably 3-glycidyloxytriethoxysilane, methyltriethoxysilane, and tetraethoxysilane. In binder formulations (BF1) and / or (BF2), preferably in and (BF2), 3-glycidyloxytriethoxysilane, methyltriethoxysilane and tetraethoxysilane are used in a mass ratio of 2 to 4:0.5 to 1.5:1, more preferably 2.5 to 3.5:0.75 to 1.25:1, and most preferably 3:1:1. In binder formulations (BF3) and / or (BF4), preferably in and (BF4), 3-glycidyloxytriethoxysilane, methyltriethoxysilane and tetraethoxysilane are used in a mass ratio of 0.5 to 1.5:1.5 to 2.5:1, more preferably 0.75 to 1.25:1.75 to 2.25:1, and most preferably 1:2:1.
[0082] It may be advantageous for the coating compositions (BM3) and (BM4) to have the same composition. Likewise, it may be advantageous for the coating compositions (BM1) and (BM2) to have the same composition. In this way, by creating layers (S1') and (S2') or (S3') and (S4'), it is possible to obtain a layer (1) or (2) of uniform composition. This can also contribute to avoiding a number of defects in the composite body.
[0083] The substrate used in the method according to the present invention is preferably a polymer nonwoven fabric comprising fibers selected from polyacrylonitrile, polyester, polyamide and / or polyolefin, preferably polyester, more preferably polyethylene terephthalate. The substrate preferably used preferably has the parameters mentioned above, in particular the parameters mentioned as preferred above.
[0084] The coating composition can be incorporated by passing it through, for example, a high-temperature air oven, an IR oven, or another oven. Coating compositions BM1 to BM4 are preferably incorporated at a temperature of 100 to 275 °C, more preferably at a temperature of 120 to 240 °C.
[0085] Alternatively, the polymer coating may be produced, for example, by applying a solution of a silicone polymer to layer (S3') or, if present, (S4') and / or the polymer layer. The solution preferably contains 3% to 10% by weight of the polymer. Suitable solvents when using silicone are particularly siloxane compounds, preferably hexamethyldisiloxane, but toluene or isooctane may also be used. When silicone is used as the polymer, it is preferable to use a multi-component system, for example, which may be supplied by Momentive, Panacol, or Evonik Hanse Chemie GmbH. For example, it is possible to use Momentive’s silicone RTV-615.
[0086] A typical addition-crosslinked silicone formulation of Evonik Hanse Chemie GmbH consists of solution A and solution B of various compositions that can be combined in a ratio of 1:10 to 10:1 depending on requirements. Here, solution A contains a platinum catalyst (platinum-siloxane complex) and may also contain vinyl-functional polydimethylsiloxane having a desired molecular weight and a desired content of vinyl groups, vinyl-functional QM resin of a desired molecular weight, and silica particles in various proportions. Solution B contains SiH-containing polydimethylsiloxane (crosslinking agent) having a desired molecular weight and desired content of SiH groups, and 0.02 wt% of an inhibitor (e.g., alkinol, divinyltetramethyldisiloxane, methylvinylcyclotetrasiloxane), and may also contain vinyl-functional polydimethylsiloxane having a desired molecular weight and desired content of vinyl groups, vinyl-functional QM resin of a desired molecular weight, and silica particles in various proportions.
[0087] The silicone formulation may also be a water-crosslinked silicone system. A polymer formulation of good suitability preferably contains 3% to 7% by weight of crosslinkable silicone in a solvent suitable for each silicone.
[0088] Drying of a coating containing or made of polysiloxane is preferably carried out at 50 to 150°C for 1 to 30 minutes.
[0089] In the preparation of the polysiloxane solution, the polymer and solution concentrations, as well as the mixing time of the polymer component in the solvent, are preferably selected so that the mixture penetrates only slightly into the pore structure of the composite body, and preferably not at all. This can be confirmed by those skilled in the art through simple preliminary experiments.
[0090] Before each application of the polymer coating, it may be advantageous to treat the layer / structure to be coated with plasma, preferably corona (air plasma). Here, it is preferable to set the power to 50 to 900 Wmin / m², preferably 100 to 300 Wmin / m², for the treatment of coatings containing rubbery polymers, and preferably 300 to 900 Wmin / m² for the treatment of ceramic layers (i.e., those containing oxide particles). Suitable equipment for corona treatment is available from Softal, Hamburg.
[0091] The method for manufacturing a composite body according to the present invention may be performed continuously or in a batch manner. The method is preferably performed by a roll-to-roll method. All steps (a) through (i) and, where appropriate, corresponding sub-steps are preferably performed in such a manner that a substrate or a substrate coated one or more times is unwound from a roll and delivered through a device in which one or more steps or sub-steps are performed, and after the integration of the applied layer, the substrate coated one or more times or the composite body of the present invention is rolled up. In the roll-up of the composite body, it may be advantageous to include an intermediate layer in the roll that prevents attachment or damage thereto to layer (S1') or (S4') or any existing polymer layer. Polyethylene terephthalate nonwoven fabric is suitable, for example, as an intermediate layer, as it is also used as a substrate. When the method according to the present invention is performed by a roll-to-roll method, the web speed is preferably 1 to 500 mm / sec, preferably 20 to 50 mm / sec.
[0092] By the method according to the present invention, it is possible to obtain a composite body according to the present invention. Accordingly, the present invention likewise provides a separation device comprising a composite body according to the present invention or a composite body manufactured according to the present invention.
[0093] A composite body according to the present invention or a composite body prepared according to the present invention may be used, for example in lipophilic nanofiltration, preferably as an organosilicon nanofiltration membrane, more preferably for the separation of organic compounds from an organic solvent-containing material stream. In this case, preferably 95% of molecules having a molecular weight greater than 800 g / mol are retained by the membrane and thus are separated from a solvent having a molecular weight of preferably less than 250 g / mol, preferably less than 150 g / mol, and more preferably less than 120 g / mol. Examples of such solvents are, for example, tetrahydrofuran, hexane, heptane, mesitylene, isopropanol, toluene, dichloromethane, acetone, and ethyl acetate.
[0094] Organic nanofiltration or separation can be performed at temperatures above 100°C, preferably above 120°C, and more preferably above 150°C. It may be advantageous if the temperature does not exceed 300°C, preferably 250°C, and most preferably 200°C. More specifically, by using a composite material according to the present invention or a composite material prepared according to the present invention as a membrane, or by using a separation device according to the present invention, it is possible to directly process a stream of material having a temperature preferably within the range mentioned above, i.e., above 100°C to 300°C, preferably above 120°C to 250°C, and more preferably above 150°C to 200°C.
[0095] The present invention is described in detail by FIGS. 1 to 4. In FIG. 1, TF represents the toluene flow rate, and in FIGS. 2 and 3, RH represents the retention, which are determined as specified in Example 5 in each case. FIG. 4 shows the basic configuration of a cross-flow filtration device used to determine the toluene flow rate and retention. What is shown is the connection of the storage vessel VB, membrane cells 1 and 2 (MZ1, MZ2), supply pump FP, permeation pump PP, and permeation vessels 1 and 2 (PB1 and PB2).
[0096] The present invention is described by the following examples, but is not limited thereto.
[0097] Examples
[0098] Table 1a: Raw materials used
[0099]
[0100]
[0101] Table 1b: Substrate materials used
[0102]
[0103] Example 1: Preparation of a composite material according to the present invention
[0104] Example 1a: Preparation of Binder Formulation I
[0105] 14.22 g of ethanol was initially filled into a 250 ml beaker along with 2.84 g of boric acid, and the mixture was stirred together using a magnetic stirrer. As soon as the boric acid was mostly dissolved, 18.16 g of GLYEO (equivalent to 15.5 g of GLYMO), 5.14 g of TEOS, and 5.14 g of MTES could be added sequentially. (This part had to be changed in each case to alter experimental conditions.) Once the mixture was sufficiently mixed, 0.03 g of water was added to initiate hydrolysis. After stirring the mixture on a magnetic stirrer for 15 hours, a second amount of water, 7.1 g, was added while stirring. Before use, the silane binder formulation prepared in this way was stirred for an additional 5 hours until the "pre-hydrolysis" subsided.
[0106] Example 1b: Preparation of Particle Formulation I
[0107] 11 kg of water was introduced into the hopbuck. 5 kg of Ox50 was added while rotating. This mixture was slowly stirred for 1 hour. To further reduce particle size, the mixture was passed through a UIP 1000 ultrasonic flow cell at a rate of 12 l / h for 6 hours. Particle size d 50 As specified in the detailed description, it was determined to be < 60 nm. The solid content was about 30 mass%.
[0108] Example 1c: Preparation of Coating Composition I
[0109] 97 g of water, 0.44 g of Dolapix CE64, and 1.84 g of a 65 mass% nitric acid solution were sequentially filled into a 1000 ml beaker and mixed together using a magnetic stirrer. 200 g of finely divided alumina (ct1200SG) was added little by little to the mixture while stirring constantly.
[0110] Once all components were weighed and sufficiently mixed, the dispersion was treated with an ultrasonic dispersion finger (Hielscher UP200) to break up any existing aggregates. After adding 42 g of ethanol to the dispersion, the mixture was stirred for at least an additional 15 hours. After 15 hours had elapsed, 13.5 g of the 30% OX50 dispersion prepared according to Example 1b, and 8.74 g of water or 4 g of Aerosil Ox50 were added together with 18 g of water. Subsequently, 52.6 g of the prepared silane binder formulation was added, and the entire dispersion was aged again in a resting state for at least 15 hours.
[0111] The resulting coating composition had a solid content of 58.7% and can be used in this form for coating experiments.
[0112] Example 1d: Preparation of Binder Formulation II
[0113] 10.45 g of ethanol was initially packed into a 250 ml beaker along with 0.84 g of boric acid, and the mixture was stirred together using a magnetic stirrer. As soon as the boric acid was mostly dissolved, 5.89 g of GLYEO, 5.0 g of TEOS, and 10 g of MTES could be added sequentially. (This step had to be changed in each case to alter experimental conditions.) Once the mixture was sufficiently mixed, 0.03 g of water was added to initiate hydrolysis. After stirring the mixture on a magnetic stirrer for 1 hour, an additional 5.19 g of deionized water was added while stirring. The silane binder formulation II prepared in this manner was stirred for an additional 15 hours before use.
[0114] Example 1e: Preparation of Coating Composition II
[0115] 101.35 g of Ox50 dispersion from Example 1b was initially filled into a 1000 ml beaker, then 299.88 g of deionized water and 3 g of a 65 mass% nitric acid solution were added sequentially, and the mixture was stirred with a magnetic stirrer for 15 hours.
[0116] 37.39 g of the prepared (silane) binder formulation II and 150.4 g of ethanol were added to the dispersion. Subsequently, this mixture was stirred for an additional 2 days.
[0117] The resulting coating composition II had an Ox50 of about 5.7% solid content and can be used in this form for coating experiments.
[0118] Example 1f: Coating process
[0119] A strip of the material to be coated (woven, nonwoven, or knitted) having a width of 10 cm and a length of about 1 m was prepared. Alternatively, it is also possible to use the result of the coating operation as described herein. However, in this case, it is preferable that the same side always be treated in subsequent processing steps.
[0120] Zehntner’s automated film stretching device was modified to use a pulley mechanism to pull the web material to be coated vertically upward at a defined speed of 42 mm / s in a dip coating device in which one side of the material web is deflected through a roll so as not to come into contact with the coating dispersion, and the other side of the material web is conveyed through a tank filled with the dispersion.
[0121] For coating, a pre-mixed dispersion (coating composition I or II) is introduced into a tank equipped with a rotating roller fitted with a material web. The filling level of the tank was adjusted so that only 45° of the roller's circumference was submerged in the solution. To ensure good delivery of the material web and to prevent the dispersion from flowing along the material web, the web tension was greater than 0.1 N / cm of the material web width. The material web is delivered through the dispersion at a speed of 42 mm / s at room temperature and standard pressure.
[0122] After the coating was completed, the material web was kept vertically suspended in a well-ventilated place for an additional 30 minutes, and then dried and integrated in a drying cabinet placed on a grid at 120°C for 1 hour.
[0123] The dried material web can be recoated, or the finished composite body can be cut or punched to size for subsequent testing or use.
[0124] To manufacture the composite material of the present invention, coatings were performed twice consecutively with coating composition I and twice with coating composition II. In any example, coating compositions I and II used may be the same or different. In order to identify the most suitable feedstock (substrate, coating composition, particle formulation, binder formulation, etc.), in preliminary experiments, coatings were also performed appropriately only once or two or more times using only coating composition I. The corresponding table lists the number of coating operations for each.
[0125] Experiments according to Example 1 were similarly performed using different particle formulations, different coating compositions I and II, different binder mixtures I and II, and different process parameters. Tables 2a to 2l show the raw materials and amounts used and the process parameters used in each case.
[0126] Table 2a: Raw materials, quantities, and various process parameters used in the manufacture of Binder Formulation I (BF-I)
[0127]
[0128] Table 2b: Raw materials and amounts used in the preparation of the particle formulation (PF) in each example
[0129]
[0130] Table 2c: Raw materials and amounts used in the preparation of coating composition I (BM-I) in each example
[0131]
[0132] Table 2d: Raw materials and amounts used in the preparation of Particle Formulation II (PF-II) in each example
[0133]
[0134] Table 2e: Raw materials and quantities used in the preparation of binder formulation II (BF-II) in each example, and optionally various parameters
[0135]
[0136] Table 2f: Raw materials and amounts used in the preparation of Coating Composition II (BM-II) or Coating Composition III (BM-III) in each example
[0137]
[0138] Table 2g: Experiment to test substrate suitability
[0139]
[0140] Table 2h: Experiment to test the suitability of coating composition I
[0141]
[0142] Table 2i: Experiment to fix the binder-to-particle ratio in Coating Composition II
[0143]
[0144] Table 2j: Experiment for immobilizing particles used in Coating Composition II
[0145]
[0146] Table 2k: Experiment for fixing the binder formulation used in Coating Composition II
[0147]
[0148] Table 2l: Experiment for fixing the binder formulation used in Coating Composition II (one-pot method)
[0149]
[0150] Example 2: Characterization of the composite body
[0151] The composite body prepared in the example was characterized as described below. The results are summarized in Table 3.
[0152] The roughness Rdq min., Rdq max., and SDQ were determined as described in detail above.
[0153] Composite bodies A to D:
[0154] All composite bodies have individual regions exhibiting low roughness (Rdq min) and regions with high roughness (Rdq max). Therefore, these values are not reliable enough to be used to make a decision regarding the optimal substrate.
[0155] From images taken within the measurement range of roughness values, it is possible to directly infer that the monofilament-based composite body D has a high overall thickness and regularly has varying heights and depths due to structural reasons. Therefore, since this material cannot achieve a smooth surface, it became subject to further evaluation.
[0156] Glass fiber weave (substrate C) has the smallest RDq min and Rdq max values compared to composite bodies A to D, and thus has very good fit due to their low roughness, but the ceramic layer on the glass fiber weave tends to crack because the filaments, especially the gaps between the individual fibers of the filaments, are not properly impregnated by the coating composition.
[0157] "Wet" nonwoven fabrics (substrates A and B) and paper are characterized by a very smooth structure (no protruding fibers) and thus possess good suitability as substrates. However, when using thick individual fibers, careful attention must be paid because the gaps between the fibers must be filled (sealed) very sufficiently. Therefore, particularly suitable substrates are PET nonwoven fabrics and carbon fiber nonwoven fabrics. Due to a smoother coating (smaller RDq and SDQ), PET nonwoven fabric is preferred for further research.
[0158] Spun-bonded nonwovens and melt-blown nonwovens have insufficient suitability, similar to dry needle felt used only in preliminary tests. Additionally, since individual coatings alone do not provide a sufficiently smooth surface, it is often necessary to select a multi-layer structure. The first layer specifically serves to fill the fiber gaps. Subsequently, the layers must be smoother.
[0159] Composite body E to J:
[0160] Dual coating with particles of various sizes indicates that the application ranges of ct1200SG (Composite Body E) and MZS1 (Composite Body H), evident from the low Gurley numbers, are best suited for achieving good ceramic filling of the substrate gaps. Finer, and larger particles lead to insufficient filling of the fiber gaps (ct 3000 SG - Composite Body G or MZS3 - Composite Body I).
[0161] The particle mixture of MZS1 and MZS3 provides relatively good surface quality (see Rdq min / max and SDQ values in this regard), but this is combined with a larger average pore radius (MFP).
[0162] Since a material having a pore size of less than 100 nm is required as a generated composite body in which the fiber interfibers of the substrate are filled to a good degree, additional work was subsequently performed, particularly for ct1200SG (composite body A or E) (however, MZS1 - composite body H is also equally suitable). In summary, d with a particle size distribution of 0.5 to 5.0 μm 50 It can be claimed that particles having can be processed.
[0163] Composite body K to Q:
[0164] When an additional layer of fine Ox50 particles is applied to the surface of ct1200SG, the average pore size decreases and the surface quality improves. The composition of particle content was varied with respect to the silane binder content.
[0165] It is not possible to show any clear trend regarding the surface quality established in the coating through changes in the silane binder content. In many additional examples, the highest binder content was used to ensure good bonding of the particles, while still achieving relatively small pores (MFP).
[0166] Composite body R to X:
[0167] When comparing the various particles used, it is first worth noting that silane binders containing silicon dioxide particles (composite bodies R, T, U) produce a very good smooth surface. However, due to their particle structure, Aerosil 90 (composite body T) and Aerosil 200 (composite body U) are not very suitable, similar to aluminum oxide Alu C (composite body S), due to aggregated primary particles. Aerosil Ox 50 (composite body R), which is tailored to the pores of the substructure to be coated, has the most suitable particles (particle size). Furthermore, Aerosil Ox 50 provides minimal pores (MFP = 0.11 μm).
[0168] Titanium dioxide P25 (composite body V) can be stabilized in the dispersion with the binder system only to a limited extent under selected conditions, and thus forms a very poor surface. Zirconium oxide from Roth (composite body W) has a fit substantially as good as Aerosil Ox50. Levasil (composite body X) has very small and sufficiently stabilized SiO2 particles, but they are so small that they penetrate the pores of the substructure (ct 1200SG). Therefore, the surface quality of these samples is almost indistinguishable from the surface quality of the ct1200SG surface (composite body E).
[0169] Composite body 2A to 2H:
[0170] It was found that relatively hydrophilic silane mixtures with relatively high proportions of TEOS and GLYEO (complex bodies 2A; 2D and 2C) produced coatings as smooth as those of complex bodies with relatively hydrophobic silane mixtures with relatively high proportions of MTES (complex bodies 2G and 2H). Only complex bodies prepared with a distinctly increased proportion of cross-linked TEOS components, such as complex bodies 2B and 2C (TEOS ratio exceeding 25% (m / m)), exhibited poorer surface quality.
[0171] The results appear to be essentially independent of the selected particle system. This implies that when using different particles, the trends associated with different silane compositions are the same, rather than representing absolute results.
[0172] Contact angle measurement impossible (nm) is shown in Table 3 when a water droplet is absorbed because the surface is hydrophilic.
[0173] Composite Body 2I and 2K:
[0174] It is not possible to prepare a mixture with aminosilane in the form described above. In order to prepare a sample, the silane mixture must be introduced without pre-hydrolysis into a vessel (one-pot method) where the particle dispersion is pre-stirred and hydrolyzed. Otherwise, the pre-hydrolyzed product solidifies, that is, forms a gel.
[0175] Observing the change in this process, it is possible in principle to replace the adhesion-promoting component GLYEO with AMEO. More specifically, it is easily possible to use other particle systems, such as P25, in this way (and by the established altered pH).
[0176] Various alkylsilanes (IBTEO) enhance the tendency to form aggregates compared to MTES. This also leads to a very non-uniform surface.
[0177] Table 3: Characterization results of composite bodies prepared in the examples and comparative examples
[0178]
[0179] Example 3: Continuous process for manufacturing a composite body
[0180] To manufacture a composite body (similar to A) according to the present invention by a continuous coating process in a corresponding manufacturing system, such as that manufactured by Matthis, for example, comprising a support unwinder, a coating device, a dryer, and a winder with tension control, the coating composition BM-Ia was prepared in a stirred 70 L stainless steel container as described above in a batch size 125 times larger. Subsequently, this was coated by a dip-coating method onto a polyester nonwoven support (05-TH-60W nonwoven) having a width of about 30 cm and a maximum length of 500 m, while maintaining a tension of > 1 N / cm of the material web width, and the support was impregnated in the process. This was introduced into an air-circulating oven 5 m long located about 50 cm downstream of the dip coater, and the composite material was dried at 140 °C. The material web velocity was 1.5 m / min.
[0181] After drying the material web, it was wound with a predetermined tension and then processed a second time in another coating operation while maintaining all process parameters. The resulting composite body K-VK-1 (similar to composite body A) is described by the parameters specified in Table 4.
[0182] a) Hydrophilic composite body
[0183] This composite body K-VK-1 was subsequently coated twice with a coating composition BM-II-e prepared on a scale approximately 10-fold magnified in the same system operating with the same mechanical parameters. The resulting continuously prepared composite body K-VK-2 (similar to composite body R) is described by the parameters specified in Table 4.
[0184] b) Hydrophobic composite body
[0185] Composite body K-VK-1 was subsequently coated twice with a coating composition BM-II-x, manufactured on a scale approximately 10-fold magnified, on the same system operating with the same mechanical parameters. The resulting continuously manufactured composite body K-VK-3 (similar to composite body 2H) is described by the parameters specified in Table 4.
[0186] Table 4: Parameters for the composite body prepared in Example 3
[0187]
[0188] Example 4: Composite body having a polysiloxane-containing polymer layer
[0189] a) Preparation of polymer solution (PL-1)
[0190] 10 g of component A (RTV-615A) in 90 g of hexamethyldisiloxane was initially filled into a round-bottom flask and heated to 60 °C. When the temperature was reached, 1 g of component B (RTV-615B) in 10 g of hexamethyldisiloxane was added. These components were thoroughly mixed under these conditions and stirred for 2 hours, then cooled and diluted with hexamethyldisiloxane to a hexamethyldisiloxane content of 92 wt% in the solution, after which the viscosity was checked. This was initially 13 mPas, changed over time, and continuously increased. This solution was processed, and as soon as the viscosity reached the range of 5 to 50 mPas, a composite body was coated. Viscosity was measured at 100 s using a rotational viscometer, model: Kinexus KNX2112m from Malvern Instruments Limited, Worcestershire, UK. -1 It was determined at a shear rate and a temperature of 25°C. The pot life of the ideal processing range is about 2 hours.
[0191] b) Preparation of polymer solution (PL-2)
[0192] A solution was obtained by combining Solution A and Solution B in a 1:1 (weight) ratio. Solution A contained 99.8 wt% of vinyldimethylpolysiloxane / vinyl-QM resin mixture VQM 906 and 0.2 wt% of catalyst 511. Solution B contained 52.99 wt% of vinyl-functional polydimethylsiloxane VS 165.000, 38.99 wt% of SiH-containing polydimethylsiloxane crosslinking agent 120, 8 wt% of vinyldimethylpolysiloxane / vinyl-QM resin mixture VQM 906, and 0.02 wt% of inhibitor methylbutinol. This mixture was diluted with hexamethyldisiloxane immediately before use so that the solution used had a hexamethyldisiloxane content of 85 wt% and a viscosity of 9 mPas. Viscosity was measured at 100 s using a rotational viscometer, model: Kinexus KNX2112m from Malvern Instruments Limited, Worcestershire, UK. -1 It was determined at a shear rate and a temperature of 25°C.
[0193] c) Preparation of polymer solution (PL-3)
[0194] 10 g of component A (RTV-615A) in 90 g of hexamethyldisiloxane was initially charged into a round-bottom flask and heated to 60 °C. Upon reaching the desired temperature, 1 g of component B (RTV-615B) was added to 10 g of hexamethyldisiloxane. These components were thoroughly mixed under these conditions and stirred for 2 hours, after which they were cooled and diluted to a hexamethyldisiloxane content of 95 wt% in the solution, after which the viscosity was checked. This was initially 6 mPas, varied over time, and continuously increased. The solution was processed, and as soon as the viscosity reached the range of 5 to 50 mPas, a composite body was coated. Viscosity was measured using a rotational viscometer, model: Kinexus KNX2112m, from Malvern Instruments Limited, Worcestershire, UK, at 100 s -1 It was determined at a shear rate and a temperature of 25°C. The pot life of the ideal processing range is about 2 hours.
[0195] d) Preparation of polymer solution (PL-4)
[0196] The solution prepared as in a) above was diluted with hexamethyldisiloxane from 92 wt% to 95 wt% hexamethyldisiloxane. After homogenizing for 2 hours, this was used for coating.
[0197] e) Coating of the composite body by a polymer
[0198] After pre-drying the composite body in a drying cabinet at 100°C for more than 2 hours, it was coated by a dip-coating method as already described in Example 1f. For this purpose, Zehntner’s automated film stretching device was modified to use a pulley mechanism to pull the web material to be coated vertically upward at a defined speed of 42 mm / s in a dip-coating device in which one side of the material web is deflected through a roll so as not to come into contact with the coating solution, and the other side of the material web is conveyed through a tank filled with the solution.
[0199] For coating, the pre-mixed solution was introduced into a tank equipped with a rotating roller fitted with a material web. The filling level of the tank was adjusted so that only 45° of the roller's circumference was submerged in the solution. To ensure good guidance of the material web and to prevent the solution from flowing along the material web, the web tension was approximately 0.1 N / cm of the material web width. The material web was guided through the solution at a speed of 42 mm / s at room temperature and standard pressure. After the coating was completed, the material web was kept suspended in the device at room temperature for an additional 15 minutes to allow most of the solvent to evaporate.
[0200] The material web was characterized only after being dried overnight at 120°C in a drying cabinet. The correlation between the composite body and the coating solution used can be seen in Table 6.
[0201] Some of the various composite materials were corona treated rather than pre-dried at 100 °C. For this purpose, the composite body was fixed with its front facing upward on a PET nonwoven fabric, an electrically nonconductive material, of Sojitz 05-TH-60W, and passed through a corona treatment system (Softal, Hamburg) at a speed of 1.5 m / min. The power of the corona treatment can be adjusted in various ways. The experimental setup can also be found in Table 6.
[0202] All composite bodies were characterized by the determination of clean gas selectivity for CO2 / CH4 and the flow rate of CO2 (as specified above) to provide evidence of defect-free coating by the polymer solution. The results are shown in Table 6.
[0203] Table 6: Experimental parameters and results from Example 4e
[0204]
[0205] Composite bodies P-VK-1 to P-VK-3 are characterized by very good resistance to handling of the composite body. This reduces the likelihood of defects or damage to the composite body occurring during introduction into a device for solvent separation. Typical defects or damage would be breakage of the ceramic due to twisting or handling with a sharp object.
[0206] All composite bodies P-VK-1 to P-VK-3 are flexible and can be wound around a bar or tube with a diameter of 15 mm or less without damage. Composite bodies P-VK-1 to P-VK-3 can be wound without damage to a minimum diameter of 5 mm or less. That the corresponding composite body is not damaged can be easily proven by determining the same clean gas selectivity before and after processing. In this case, a 2-unit reduction in clean gas selectivity is evaluated as a "defect of the composite body."
[0207] Due to the flexibility of the composite body, they can be introduced in a very simple manner in the form of typical modules for flat membranes, and are particularly suitable for use in spirally wound modules, plate and frame modules, pocket modules, and other devices designed for flat membranes.
[0208] Example 5: Test of a composite body having a polysiloxane-containing polymer layer
[0209] For further characterization, a portion of the membrane was examined by a method known as MWCO (Molecular Weight of Fraction) in toluene. This method is described specifically in WO 2011 / 067054 A1, as well as in the literature [Journal of Membrane Science 291 (2007) 120-125]. For this purpose, the membrane was tested in cross-flow filtration using toluene as the solvent, dissolving polystyrene of different molecular weights at a total concentration of 1 g / L. The basic configuration of this apparatus is shown in Fig. 4. The permeate flow (toluene) was monitored and quantified by gravimetric measurement for 3 hours. After 3 hours, a portion of the final collected permeate was taken and collected in a separate sample bottle for molecular weight determination by an HPLC system.
[0210] Unless otherwise specified, the test is performed in a cross-flow filtration device at 30 bar (30 * 10) while continuously pumping the permeate stream back into the storage vessel by a pump. 5 The experiments were performed at a membrane penetration pressure (TMP) of Pa and a temperature of 30 °C. The membrane cells used in these experiments were supplied by Evonik Membrane Extraction Technologies.
[0211] Table 7 provides the molecular weight at which 90% retention is achieved as a result of these tests. Some of the tested membranes were pretreated (Examples 5a and 5b). The results of these tests are shown below, and in Figures 1 to 3 and Table 7.
[0212] a) Thermal stability
[0213] A portion of the composite body obtained in Example 4e was stored in a drying cabinet at 150 °C for 72 hours (composite body: P-VK-1-temp). Subsequently, the characterization of membrane properties was repeated. There was no significant change in flow rate or retention compared to the composite body that was not thermally treated.
[0214] b) Solvent stability
[0215] The composite body obtained in Example 4e was stored in mesitylene at 150 °C for 72 hours (composite body: P-VK-1-solv). Subsequently, the characterization of membrane properties was repeated. There was no significant change in flow rate or retention compared to the results of the untreated composite body.
[0216] c) Separation characteristics at high temperatures
[0217] The composite body obtained in Example 4e was subjected to 30 bar (30 * 10 5 It was used at a membrane penetration pressure of Pa and high temperature. Here, there were distinct changes in flow rate and only slight changes in retention. The measurement results regarding permeability characteristics for toluene and retention for polystyrene are presented below, along with the examination of specimen P-VK-1-130 ℃ at a temperature of 130 ℃, where specimen P-VK-1-30 ℃ is a comparative value to the specimen examined at 30 ℃. The examination was always performed for 3 hours at 5 bar (5 * 10⁻⁶). 5 The procedure was performed at a permeate pressure of Pa, and the flow rate was recorded after 3 hours. The results of the retention process can be seen in Figure 3. The results of determining the toluene flow rate and retention can be seen in Table 7.
[0218] Table 7: Determination results of toluene flow rate and retention
[0219]
[0220] The results of FIGS. 1 to 3 and Table 7 show that, due to the ceramic structure of the composite bodies P-VK-1 to P-VK-3, their thickness and porosity do not substantially change under compressive stress at high temperatures. This is important for ensuring that the entire composite body according to the present invention has a substantially constant toluene flow rate even under high compressive stress at high temperatures, and that the flow is not reduced at higher pressures due to the compressive porous structure.
[0221] Example 6: Investigation of changes in particle size distribution at different processing stages
[0222] In addition, a study was conducted on the extent to which the particle size distribution changes during the preparation process of the coating composition. For this purpose, the particle formulation (PF) used in the previous example was compared with their average particle size (d 50 ) was analyzed. The measurement results are shown in Table 8a. Subsequently, a coating composition (BM) was prepared as described in the previous example. The average particle size of the coating composition was measured. The measurement results are shown in Table 8b. Table 8c shows the d of the particles used depending on the manufacturer. 50 Record the value.
[0223] The quantitative evaluation of the measurements is shown in Table 9.
[0224] In summary, from the results shown in Tables 8a, 8b, 8c, and 9, it can be inferred that the difference in particle size at different treatment stages (PF to BM) is due only to the degree of stabilization of the particles in each dispersion.
[0225] Table 8a: Measurement of average particle size of particulate formulations (PF).
[0226]
[0227] Table 8b: Measurement of average particle size of coating composition (BF)
[0228]
[0229] Table 8c: Average particle size by manufacturer
[0230]
[0231] Table 9: Evaluation of Measurement Results
[0232]
Claims
Claim 1 A porous layer (1) comprising oxide particles bonded to a substrate comprising one or more oxides selected from oxides of elements Al, Zr and Si, on a porous substrate comprising fibers of an electrically nonconductive material and within the gaps of the substrate, and having an additional porous layer (2) comprising oxide particles bonded to the layer (1), comprising one or more oxides selected from oxides of elements Al, Zr and Si, on at least one plane, wherein the oxide particles present in the layer (1) have an intermediate particle size larger than the oxide particles present in the layer (2), and the intermediate particle size (d) of the oxide particles in the layer (1), determined according to ISO 13320 50 The intermediate particle size (d) of oxide particles in layer (2), which is 0.5 to 4 μm and is determined according to ISO 13320. 50 ) is 0.015 to 0.15 μm, or 0.04 to 0.06 μm, and is characterized by having one or more polymer coatings (PB) containing polysiloxanes on or above the layer (2), and the substrate is characterized by being a nonwoven fabric, knit, or laminated scrim, wherein “flexible” means a flexible composite body that can be wound around a bar or tube without damage, with a diameter of 15 mm or less. Claim 2 In claim 1, the composite body is at 130 ℃ and 30 bar (30*10 5 A composite body characterized by having a toluene flow rate of greater than 130 L / ㎡h, greater than 250 L / ㎡h, greater than 300 L / ㎡h, or greater than 400 L / ㎡h at a membrane penetration pressure of Pa. Claim 3 A composite body according to claim 1, characterized in that the composite body has a thickness of 100 to 400 μm, 125 to 200 μm, or 130 to 170 μm. Claim 4 A composite body according to claim 1, characterized in that the fiber has a fiber dimension of 1 to 200 g / km. Claim 5 A composite body according to claim 1, characterized in that the substrate has a thickness of 50 to 150 μm or 100 to 130 μm and a base weight of 40 to 150 g / m², 50 to 120 g / m², 50 to 100 g / m², or 60 g / m². Claim 6 A composite body according to claim 1, characterized in that the composite body has an average pore size of 60 to 140 nm or 75 to 130 nm, and the average pore size is determined by a gas flow pore measurement method. Claim 7 A composite body according to claim 1, characterized in that the composite body has a surface roughness Sdq of less than 10 μm or less than 8 μm on the surface of layer (2). Claim 8 A method for manufacturing a flexible composite body, characterized by having the following steps: (a) applying a coating composition (BM1) to a substrate having fibers and gaps between fibers and within the substrate, wherein the coating composition (a1) is selected from oxides of the elements Al, Zr and / or Si, and has an intermediate particle diameter (d) of 0.5 to 4 μm. 50 A dispersion of oxide particles (D1), (a2) produced by mixing oxide particles having ) with water, an inorganic acid, and a dispersion aid, selected from oxides of elements Al, Zr and / or Si, with an intermediate particle diameter (d) of 15 to 150 nm, or 40 to 60 nm. 50 (a3) a dispersion of oxide particles (D2) produced by mixing oxide particles having ) with water, formed by combining a binder formulation (BF1) produced by mixing two or more organic functional silanes with an alkanol, an inorganic acid, and water, (b) a step of forming a first layer (S1') by incorporating a coating composition (BM1) at a temperature of 100 °C to 275 °C, or 120 °C to 240 °C, (c) optionally applying a coating composition (BM2) to at least the layer (S1'), wherein the coating composition (BM2) is (c1) selected from oxides of elements Al, Zr and / or Si, and has an intermediate particle diameter (d) of 0.5 to 4 μm. 50 A dispersion of oxide particles (D3), (c2) produced by mixing oxide particles having ) with water, an inorganic acid, and a dispersion aid, selected from oxides of elements Al, Zr and / or Si, with an intermediate particle diameter (d) of 15 to 150 nm, or 40 to 60 nm. 50 (D4), (c3) a dispersion of oxide particles produced by mixing oxide particles having ) with water, produced by combining a binder formulation (BF2) produced by mixing two or more organic functional silanes with an alkanol, an inorganic acid, and water; (d) optionally a step of producing a second layer (S2') by incorporating the coating composition (BM2) at a temperature of 100 °C to 275 °C, or 120 °C to 240 °C; (e) a step of applying the coating composition (BM3) to the layer (S1') or, if present, the layer (S2'), wherein the coating composition (BM3) is selected from oxides of elements Al, Zr and / or Si, and has an intermediate particle diameter (d) of 15 to 150 nm, or 40 to 60 nm, and is formed by mixing water and an inorganic acid (e1). 50 (f) a step of forming a layer (S3') by incorporating the coating composition at a temperature of 100 °C to 275 °C, or 120 °C to 240 °C, wherein the coating composition (BM4) is optionally applied to the layer (S3'), the coating composition (BM4) is formed by combining water and an inorganic acid (g1) a step of forming an aqueous dispersion (D6) comprising oxide particles having an intermediate particle diameter of 15 to 150 nm, or 40 to 60 nm, selected from oxides of elements Al, Zr, and / or Si, and ethanol, and a step of incorporating the coating composition at a temperature of 100 °C to 275 °C, or 120 °C to 240 °C, (g) optionally forming the coating composition at a temperature of 100 °C to The method comprises the steps of: (i) forming a layer (S4') by incorporating at a temperature of 275 ℃, or between 120 ℃ and 240 ℃; and (i) applying a polymer coating containing polysiloxane to the layer (S3') or, if present, to the layer (S4'), wherein the organic functional silane used is characterized as being 3-glycidoxytriethoxysilane, methyltriethoxysilane, and tetraethoxysilane, and wherein the substrate used is characterized as being a polymer nonwoven fabric comprising fibers selected from polyacrylonitrile, polyester, polyamide, and / or polyolefin, wherein "flexible" means that the composite body can be wound around a bar or tube with a diameter of 15 mm or less without damage. Claim 9 A method according to claim 8, characterized in that 3-glycidyloxytriethoxysilane, methyltriethoxysilane and tetraethoxysilane are used in binder formulations (BF1) and (BF2) in a mass ratio of 2 to 4:0.5 to 1.5:1, 2.5 to 3.5:0.75 to 1.25:1, or 3:1:
1. Claim 10 A method according to claim 8, characterized in that 3-glycidyloxytriethoxysilane, methyltriethoxysilane and tetraethoxysilane are used in binder formulations (BF3) and (BF4) in a mass ratio of 0.5 to 1.5:1.5 to 2.5:1, 0.75 to 1.25:1.75 to 2.25:1, or 1:2:
1. Claim 11 A method according to claim 8, characterized in that the coating compositions (BM3) and (BM4) have the same composition. Claim 12 A method according to claim 8, characterized in that the coating compositions (BM1) and (BM2) have the same composition. Claim 13 A method according to claim 8, characterized in that the integration is performed by passing through a high-temperature air oven, an IR oven, or another oven. Claim 14 A composite body characterized by being used in lipophilic nanofiltration in any one of claims 1 to 7. Claim 15 A composite body manufactured by the method according to claim 8, characterized by being used in lipophilic nanofiltration. Claim 16 A composite body according to claim 14, characterized in that lipophilic nanofiltration is performed at a temperature greater than 100°C, greater than 120°C, or greater than 150°C. Claim 17 A composite body according to claim 15, characterized in that lipophilic nanofiltration is performed at a temperature greater than 100°C, greater than 120°C, or greater than 150°C. Claim 18 A separation device comprising a composite body manufactured according to any one of claims 1 to 7 or according to any one of claims 8 to 13. Claim 19 delete
Citation Information
Patent Citations
Separator with asymmetric porous structure for electrochemical cells
JP2006507635A
Ceramic membranes with improved adhesion to plasma-treated polymeric supporting material and production and use
JP2008208511A
Hybrid Membrane, Method of Manufacture and Use of Membrane
JP2005525224A
